PENGEMBALIAN BERKAS KLAIM PASIEN PESERTA JAMINAN KESEHATAN NASIONAL (JKN) DI RSUD SULTAN SYARIF MOHAMAD ALKADRIE KOTA PONTIANAK - Andi Sulaimana; Andreasta Meliala; Julita Hendrartini (Journal of Health Service Management, 2019)
Background: Approach of managed care in the National Health Insurance Program (JKN) puts hospitals as a health facility referral with the prospective payment system. Treatment of patients should be done and handled in primary health facilities. Although the number of patient referral to hospitals in JKN era remains high. The impact of the hospital is faced with an increase in claims bills to BPJS Kesehatan. By 2016 in RSUD Pontianak it was noted that 6.98% of the income came from JKN hospital patients which had not been paid by BPJS Kesehatan, so some were returned. A research needs to be conducted on the cause of the returned claim file from BPJS Kesehatan verifier to RSUD Pontianak. Objective: To find out the cause of the claims pending in RSUD Pontianak. Methods: The research is an exploratory case study with a single case study design approach. Results: The claim process at RSUD Pontianak is still not as good as never completed every month. Most of the causes of returned claims are administrative errors and medical reasons. Maladmin istration in the form of typing errors, dates, but a sign from the doctor. Medical reasons include coding disagreements, differences in perceptions about specific inspection directions, lack of support, differences in perceptions about secondary diagnostic inputs. Performance coding is limited to differences in perceptions between Coder and BPJS Kesehatan Verifier, positive physician response to file claims reversed, BPJS Kesehatan Verifier perceptions are constrained in capacity, differences in educational background, differences in understanding with Coder on Reselected Coding, and differences in regulatory implementation in the claims process. Conclusion: Technical error of claims administration process, difference of perception of coding, difference of comprehension about complementary examination, special treatment and secondary diagnosis input, and difference of perception to JKN regulation on verifier of cause of claim file of JKN patients return to RSUD Pontianak.